2006
DOI: 10.1590/s0100-55022006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Promoção da saúde e cultura cidadã envolvendo uma abordagem oftalmológica em escolares na Colônia Antônio Aleixo (CAA), Manaus-AM: uma experiência no ensino médico

Abstract: Objetivou-se promover a capacitação de alunos de Medicina da disciplina de Saúde Coletiva da Universidade Federal do Amazonas e comunidade para o desenvolvimento de uma cultura cidadã dentro do paradigma socioecológico, identificando-se os problemas oftalmológicos nos escolares da comunidade. Foram realizadas visitas domiciliares semanais e discutidas questões relevantes para a saúde dos moradores e problemas da localidade, na CAA, bairro periférico de Manaus. Escolares de 4 a 14 anos dessa comunidade foram tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…19 Most studies indicate that women of all ages in all regions of the world have a considerably higher risk of being visually impaired in relation to men, especially in the case of higher life expectancy, and in those societies with considerable reduction of purchasing power, due to the limited access to health services. 5 The low frequency of reduced visual acuity found in the present study corroborates the results of similar studies, such as those performed in Londrina (PR) with 17.1%, 3 in Pelotas (RS) with 15.1%, 1 in Sorocaba (SP) with 13.1%, 20 in Manaus (AM) with 7%, 21 in Passo Fundo (RS) with 10.9%, 8 in Pouso Alegre (MG) with 11.4%, 19 in Curitiba (PR) with 7.03%, 18 and in Belo Horizonte (MG) with 10.3%. 9 In any case, it is suggested that joint prevention programs of the Health and Education Departments be strengthened, in order to guarantee continuous decline of the visual deficit and consequent improvement of the students eye health.…”
Section: Discussionsupporting
confidence: 91%
“…19 Most studies indicate that women of all ages in all regions of the world have a considerably higher risk of being visually impaired in relation to men, especially in the case of higher life expectancy, and in those societies with considerable reduction of purchasing power, due to the limited access to health services. 5 The low frequency of reduced visual acuity found in the present study corroborates the results of similar studies, such as those performed in Londrina (PR) with 17.1%, 3 in Pelotas (RS) with 15.1%, 1 in Sorocaba (SP) with 13.1%, 20 in Manaus (AM) with 7%, 21 in Passo Fundo (RS) with 10.9%, 8 in Pouso Alegre (MG) with 11.4%, 19 in Curitiba (PR) with 7.03%, 18 and in Belo Horizonte (MG) with 10.3%. 9 In any case, it is suggested that joint prevention programs of the Health and Education Departments be strengthened, in order to guarantee continuous decline of the visual deficit and consequent improvement of the students eye health.…”
Section: Discussionsupporting
confidence: 91%
“…In Mesopotamia irrigation systems were already used (4,000 BC). The first sewer galleries (3,200 BCE) date from India. The Sumerians (5,000-4,000 BC) constructed irrigation canals, galleries, settlements, cisterns, reservoirs, wells, tunnels and aqueducts ".…”
Section: Basic Sanitationmentioning
confidence: 99%
“…But it was a place with no connection, land route to the city, since there lived those affected by leprosy, disease, which since biblical times proves awe in the population and their sufferers, are removed from the city. It was only in 1972 that the first access road was built, by land, being paved during the management of Jorge Teixeira, in the city of Manaus [3]. Beginning in the early 1980s, people without the disease's prevalence began to fix housing on the site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation